PENGARUH BEBAN KERJA, KOMITMEN ORGANISASI, DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN KLINIK PENTA MEDICA - Kadek Yuliari; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This research aims to analyze the influence of workload, organizational commitment and work supervision on the performance of Penta Medica Clinic employees. The number of samples used was 38 people using the saturated sample method. Data collection was carried out using a 5 point Likert scale questionnaire. The research objects are workload, organizational commitment, work supervision and employee performance. The data analysis technique uses multiple linear regression tests. Hypothesis testing is carried out using the t-test. The research results show that workload has a negative and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, work supervision has a positive and significant effect on employee performance.